Dielectric characterization of liquid containing low alcoholic content for potential halal authentication in the 0.5-50 GHz range - Zainal Abidin, Zurina; Omar, Fatin Nordalila; Yogarajah, Pavithiran; Awang Biak, Dayang Radiah; Che Man, Yaakob (Science Publications, 2014)
A potential method for detection and discrimination of alcoholic containing drinks for halal authentication using dielectric properties has been investigated. Behaviors of several pure alcohols, alcohol solution in water and also liquids with alcoholic contents were studied for verification purpose. Dielectric constant and dielectric loss factor for low concentration of ethanol solutions were measured over the microwave frequency from 0.5 to 50 GHz. The measurements were extended to several commercial alcoholic beverages. The results showed that dielectric properties manage to discriminate alcohol content until the lowest concentration studied of 0.5% in water mixture at frequency range of 10-25 GHz. Beyond this limit, solution is considered as alcoholic drinks.